158 ANTENATAL INDOMETHACIN SUPPRESSES LUNG MATRIX METALLOPROTEINASE ACTIVITY AND VASCULAR ENDOTHELIAL GROWTH FACTOR LEVELS IN FETAL RABBITS. (1st January 2006) - Gharraee, Z.; Beharry, K. D.; Fortson, W.; Hasan, J.; Jan, A.; Abad-Santos, P.; Sills, J. H.; Valencia, A. M.; Modanlou, H. D.
Abstract : Oral indomethacin (OI) has been shown to increase saccular wall mass and decrease airspace in fetal rat lungs, implicating an etiologic relationship with persistent pulmonary hypertension (PPHN). Normal fetal lung maturation is associated with increased breakdown and remodeling of the lung basement membrane and extracellular matrix, as well as microvascular maturation. These processes are regulated, in part, by matrix metalloproteinases (MMPs) and vascular endothelial growth factor (VEGF). We tested the hypothesis that maternal administration of OI suppresses MMP activity and VEGF levels in fetal rabbit lungs, in a rabbit model for RU486-induced preterm birth. We also examined and compared the effects of vaginally administered indomethacin. Pregnant rabbits ( n = 6/group) were injected with a single 50 mg IM dose of RU486 at 24 days of a 30- to 32-day gestation. Immediately following, the animals received either (1) OI (20 mg in a vehicle suspension); (2) a mixture of methylcellulose and polysorbate 80 (OV, vehicle); a vaginal suppository of indomethacin (VI, 20 mg in cocoa butter); or a suppository of cocoa butter only (placebo, VP), once daily for 2 days. At delivery, lung homogenates were examined for MMP-2 and MMP-9 activity, tissue inhibitor of metalloproteinase (TIMP)-1 and TIMP-2 levels, and VEGF levels. Lung MMP-9 activity (ng/mg protein) was suppressed with OI (0.11 ± 0.003 vs 0.17 ± 0.005, p < .001) and VI (0.093 ± 0.008 vs 0.25 ± 0.008, p < .01) compared to OV and VP, respectively. In contrast, TIMP-1 (3.7 ± 0.87 vs 0.89 ± 0.09, p < .01) and TIMP-2 (43.3 ± 2.7 vs 22.4 ± 2.9, p < .001) levels (ng/mg protein) were elevated with OI only compared to OV resulting in suppression of MMP-2/TIMP-2 (0.23 ± 0.01 vs 0.55 ± 0.01, p < .001) and MMP-9/TIMP-1 (0.07 ± 0.002 vs 0.21 ± 0.007, p < .001) ratios. Lung VEGF levels (pg/mg protein) were suppressed with both OI (1.79 ± 0.11 vs 2.5 ± 0.07, p < .05) and VI (2.2 ± 0.2 vs 2.9 ± 0.16, p < .05). We conclude that the combined suppression of lung MMP activity and VEGF synthesis with OI may be responsible for immature, thickened saccular walls and the development of PPHN.